Challenges of educational migration of Tuvan youth: Demographic aspect - Rostovskaya, Tamara K.; Vasilieva, Ekaterina N. (The New Research of Tuva, 2023)
The purpose of the article is to study institutional challenges and their influence on the educational migration of Tuvan young people in the Republic of Tuva in 2018–2022. In the article, institutional challenges are interpreted as: 1) the ratio of the number of young people to the number of state-funded places in educational institutions of the Republic; 2) tuition fee in institutions of secondary and higher education in the region and the level of income of the population; 3) the youth unemployment rate. The sources of information include websites of educational institutions in the studied subject of the Russian Federation on the Internet, statistical data on the income of the population, the labor market and demographic indicators of Tuva. The research methods are logical and statistical ones, as well as document analysis.The indicators of the age and gender structure of the population of the Republic of Tuva show that in the demographic structure of the population, the proportion of young people applying for a place in secondary vocational and higher educational institutions will be increasing during the next 10 years. At the present stage of development, there are not enough educational resources in Tuva to meet the demands of applicants on the regional market of educational services. The limited number of budget-funded places and the high cost of education are the reasons for the formation of life strategies of young people aimed at implementing plans for educational migration to more prosperous regions of Russia. Low incomes of the population are an obstacle to obtaining higher and secondary vocational education for the Tuvan youth. Using the example of a household model that consists of parents and three dependent children, the authors have calculated that the members of such a household will not be able to afford to pay for the education of one child under a service contract at their expense. The young people involuntarily abandon the idea to migrate after acquiring secondary education due to financial problems. But this does not guarantee that a young person will not leave for another region searching for a work. An analysis of the situation on the Tuvan labor market shows that the unemployment rate remains high.
Keywords: Republic of Tuva; internal migration; educational migration; youth migration; institutional challenge; educational institution; income level of the population; labor market